Belarus Public Expenditure Review : Enhancing Public Services in Times of Austerity - World Bank (Washington, Dc, 2013)
This report is the second volume of the programmatic Public Expenditure Review (PER) in Belarus. In 2010 the Ministry of Finance requested that the Bank provide sequenced and targeted advice on the fiscal reform options across priority areas of the budget. Responding to this request, a programmatic PER was agreed upon. The first volume was delivered in November 2011 and focused on providing policy options for a sustainable pension system, better targeted social assistance and rationalization of energy and agricultural subsidies. The objective of this volume is to identify reform opportunities to enhance the quality of key public services in a fiscally constrained environment. Specifically, the second PER will analyze three key areas of the budget: intergovernmental fiscal relations and public spending in the education and health sectors. These three areas were chosen because they are significant from a fiscal perspective. More than half of government spending is channeled through sub-national governments, while education and health spending together account for a quarter of government spending (largely at the sub-national level). Beyond their fiscal importance, enhancing the quality and efficiency of spending in these sectors is critical for improving living standards and human capital in Belarus. However, since public finances are expected to remain tight for some years to come, expenditures, even in priority sectors such as health and education, will remain constrained. Therefore, the focus of this report is on the productivity of public spending. The primary thrust is to enhance the allocated and operational efficiency of resources to allow for improved quality of services and social outcomes while containing overall costs. The report also examines the impact of Belarus changing demographic profile, which will have a significant and lasting impact on demand for both health and education services. The report has four chapters. The first chapter reviews recent macro-economic and fiscal developments, and in particular the impact of the macro-economic crises on public finances and its implications for fiscal policy choices going forward. The second chapter examines intergovernmental fiscal relations and the fiscal incentives they create for sub-national governments. The third chapter looks at health sector outcomes and expenditures to identify opportunities for improved spending efficiency and sustainable health care financing. The fourth chapter is focused on resource allocation and utilization in the education sector to provide options for improved efficiency and effectiveness of education spending.